Continuum‐scale investigation of evaporation from bare soil under different boundary and initial conditions: An evaluation of nonequilibrium phase change. Issue 9 (18th September 2015) - Trautz, Andrew C.; Smits, Kathleen M.; Cihan, Abdullah
Abstract Evaporation and condensation in bare soils govern water and energy fluxes between the land and atmosphere. Phase change between liquid water and water vapor is commonly evaluated in soil hydrology using an assumption of instantaneous phase change (i.e., chemical equilibrium). Past experimental studies have shown that finite volatilization and condensation times can be observed under certain environmental conditions, thereby questioning the validity of this assumption. A comparison between equilibrium and nonequilibrium phase change modeling approaches showed that the latter is able to provide better estimates of evaporation, justifying the need for more research on this topic. Several formulations based on irreversible thermodynamics, first‐order reaction kinetics, or the kinetic theory of gases have been employed to describe nonequilibrium phase change at the continuum scale. In this study, results from a fully coupled nonisothermal heat and mass transfer model applying four different nonequilibrium phase change formulations were compared with experimental data generated under different initial and boundary conditions. Results from a modified Hertz‐Knudsen formulation based on kinetic theory of gases, proposed herein, were consistently in best agreement in terms of preserving both magnitude and trends of experimental data under all environmental conditions analyzed. Simulation results showed that temperature‐dependent formulations generally better predict evaporation than formulations independent of temperature. Analysis of vapor concentrations within the porous media showed that conditions were not at equilibrium under the experimental conditions tested.